The Dynamics of Soil Organic Matter Fractions in Cacao-Based Agroforestry Systems - Sari, Rika Ratna; Sapulete, Carla Leany; Saputra, Danny Dwi; Hairiah, Kurniatun (JOURNAL OF TROPICAL SOILS, 2025)
Soil degradation is an important problem affecting crop production, especially in cocoa agroforestry systems, where soil health is crucial for optimal results. However, the effect of land management on changes in soil organic matter (SOM) content is often not visible through measurements of total soil organic carbon (SOC) content. This study investigates the distribution of soil organic matter fractions across various land-use gradients and soil depths in cacao-based agroforestry landscapes in Southeast Sulawesi, Indonesia. Soil samples were collected from three villages representing different parts of a watershed and subjected to density fractionation to separate light (LF), intermediate (IF), and heavy (HF) fractions. Our results indicate that remnant forests (RF) maintain higher total SOM fractions, followed by cacao-based complex and simple agroforestry (CAF, SAF), particularly in the 0-10 cm soil depth. In contrast, annual crops (CR), exhibit the lowest SOM fractions. Standing litter and decomposition rates significantly influence the LF, while HF shows minimal variation across land-use systems, suggesting long-term stability. The LF also strongly correlates with SOC content, highlighting its responsiveness to recent organic inputs. The findings underscore the importance of diverse litter inputs and tree diversity in enhancing SOM fractions and SOC content in agroforestry systems. The study concludes that complex cacao-based agroforestry systems can effectively mimic natural forest conditions, promoting soil health. These insights provide valuable knowledge for sustainable land management practices to mitigate soil degradation and improve soil quality in cacao production systems.